Caricom's trade 1985-1990: a quick reference to some summary data (CCS GeorgetownGY, 1993)
Provides a ready reference to statistics on the value of Caricom's imports and exports; Caricom's trade with Canada, USA, EEC, UK, Latin America, Venezuela, Japan; and Intra-Caricom trade.
DC